PENGARUH PERTUMBUHAN PERUSAHAAN, LIKUDITAS DAN KUALITAS AUDIT TERHADAP OPINI AUDIT GOING CONCERN: STUDI EMPIRIS PADA INDUSTRI PROPERTI DAN REAL ESTATE DI BURSA EFEK INDONESIA - Kristiani, Mega; Lusmeida, Herlina (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
This study aims to see the effect of corporate growth, liquidity and audit quality to going concern audit opinion.  The independent variables in this research are company growth, liquidity and audit quality. The dependent variable is going concern audit opinion. The sample in this research is property and real estate company which is listed in Indonesian Stock Exchange (IDX) from 2010-2016. The total population of companies that meet the criteria is 10 companies with the number of observations is 70 samples of the company. Sample chosen by using purposive sampling method and sample processed by using program SPSS version 22. Technical analysis of data used in this research is logistic regression analysis technique.  The results of this study indicate the company's growth and liquidity does not affect the going concern audit opinion, while the audit quality has an effect on going concern audit opinion .